2020
DOI: 10.1186/s40478-020-00906-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of an osseous metastasis in glioblastoma during checkpoint inhibition: potential mechanisms of immune escape

Abstract: Peripheral metastases of glioblastoma (GBM) are very rare despite the ability of GBM cells to pass through the blood-brain barrier and be disseminated through the peripheral blood. Here, we describe a detailed genetic and immunological characterization of a GBM metastasis in the skeleton, which occurred during anti-PD-1 immune checkpoint therapy. We performed whole genome sequencing (WGS) and 850 K methylation profiling of the primary and recurrent intracranial GBM as well as one of the bone metastases. Copy n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…In the pulmonary metastasis model of 4T1, treatment with CGA significantly decreased metastatic nodules in lung tissues. Tumor immune escape, which is featured as suppressive antitumor immunity, is responsible for tumor malignancy and distant metastasis ( 47 ). Based on the efficient anti-metastasis efficacy of CGA, the present study investigated the effect of CGA on antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In the pulmonary metastasis model of 4T1, treatment with CGA significantly decreased metastatic nodules in lung tissues. Tumor immune escape, which is featured as suppressive antitumor immunity, is responsible for tumor malignancy and distant metastasis ( 47 ). Based on the efficient anti-metastasis efficacy of CGA, the present study investigated the effect of CGA on antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Although GBM cells can pass through the BBB and be disseminated throughout the peripheral blood ( 7 ), extracranial metastasis of GBM is rare, with a reported incidence of approximately 0.4% to 2% ( 6 , 18 , 19 ). This rare phenomenon is also attributed to the absence of lymphatics in the brain ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Later studies indicated a lymphatic pathway of GBM metastasis (30). Malte Mohme et al described that extracranial metastasis of GBM may also be related to genetic drivers and immune escape (7). GBM metastasizing to the distal limbs has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing immunotherapy for gliomas has also attracted extensive investigation (Ogbomo et al, 2011;Topalian et al, 2015). Transcriptional characteristics can also reflect the status of tumor immune-microenvironment, which is critical for developing immunotherapy for IDH-wild type gliomas (Zhang et al, 2017;Cai et al, 2018;Martinez-Lage et al, 2019;Mohme et al, 2020;Zha et al, 2020). Here, we observed a positive correlation between signature risk scores and the number of immune-infiltrating cells in IDH-wild type WHO grade IV gliomas.…”
Section: Discussionmentioning
confidence: 99%